Reviews in fluorescence 2009 - Geddes, Chris D. (Reviews in Fluorescence, 2011)
Reviews in Fluorescence 2009, the sixth volume of the book serial from Springer, serves as a comprehensive collection of current trends and emerging hot topics in the field of fluorescence and closely related disciplines. It summarizes the year?s progress in fluorescence and its applications, with authoritative analytical reviews specialized enough to be attractive to professional researchers, yet also appealing to the wider audience of scientists in related disciplines of fluorescence. Reviews in Fluorescence offers an essential reference material for any lab working in the fluorescence field and related areas. All academics, bench scientists, and industry professionals wishing to take advantage of the latest and greatest in the continuously emerging field of fluorescence will find it an invaluable resource.    offers an essential reference material for any lab working in the fluorescence field and related areas. All academics, bench scientists, and industry professionals wishing to take advantage of the latest and greatest in the continuously emerging field of fluorescence will find it an invaluable resource.       ? Key features · Chapters authored by known leading figures in the fluorescence field. · New volume publishes annually · Comprehensive coverage of the year?s hottest and emerging topics. · Accessible utility in a single volume reference. · Reviews in Fluorescence 2009 topics include: · Hot electron-Induced Electrogenerated Chemiluminescence · Time-correlated, single-photon counting methods in endothelial cell mechanobiology. · Origin of Tryptophan Fluorescence · Protein Folding, Unfolding and Aggregation Processes revealed by Rapid Sampling of Time-Domain Fluorescence. Chapters authored by known leading figures in the fluorescence field. · New volume publishes annually · Comprehensive coverage of the year?s hottest and emerging topics. · Accessible utility in a single volume reference. · Reviews in Fluorescence 2009 topics include: · Hot electron-Induced Electrogenerated Chemiluminescence · Time-correlated, single-photon counting methods in endothelial cell mechanobiology. · Origin of Tryptophan Fluorescence · Protein Folding, Unfolding and Aggregation Processes revealed by Rapid Sampling of Time-Domain Fluorescence.